Serum antibody response to BNT162b2 after natural SARS‐CoV‐2 infection. (1st August 2021) - Perkmann, Thomas; Perkmann‐Nagele, Nicole; Koller, Thomas; Mucher, Patrick; Radakovics, Astrid; Wolzt, Michael; Wagner, Oswald F.; Binder, Christoph J.; Haslacher, Helmuth
Abstract: Background: There is preliminary evidence that individuals with previous SARS‐CoV‐2 infections exhibit a more pronounced antibody response. However, these assumptions have not yet been supported by data obtained through various CE‐marked tests. This study aimed to close this gap. Methods: Sixty‐nine seronegatives and 12 individuals post‐SARS‐CoV‐2 infection (tested by CE‐labelled Roche NC immunoassay or PCR‐confirmed assay) were included 21 ± 1 days after receiving the first dose of the Pfizer/BioNTech BNT162b2 vaccine. Antibody response to viral spike protein (S) was assessed by CE‐labelled Roche S and DiaSorin S1/S2 assays and by a surrogate virus neutralization test (sVNT). Results: After a single dose of BNT162b2, individuals after natural SARS‐CoV‐2 infection presented with markedly higher anti‐S levels than naïve individuals (Roche S: 9078.5 BAU/mL [5267.0‐24 298.5] vs 79.6 [24.7‐142.3]; and DiaSorin S1/S2: 1465.0 AU/mL [631.0‐5365.0] vs 63.7 [47.8‐87.5]) and showed all the maximum observed inhibition activity in the sVNT (98%), without overlaps between groups. There was a trend for higher responses in those with a more distant infection, although not statistically significant. The relative antibody increase after dose 2 was significantly higher among naïve individuals (25‐fold), but antibody levels remained below that of seropositives. Conclusions: Compared with naïve individuals, seropositives after natural SARS‐CoV‐2 infection presented with a substantially higher antibody response already after dose 1 of BNT162b2, as measured by two CE‐marked in vitro diagnostic tests and a sVNT. These results should stimulate discussion and research on whether individuals after previous SARS‐CoV‐2 infection would benefit from a two‐part vaccination schedule or whether these currently much‐needed second doses could be saved.